Cyberbullying in College - Carlos P. Zalaquett; SeriaShia J. Chatters (2014)
Cyberbullying is commonly presented as affecting K-12 populations. Current research suggests cyberbullying continues in college. A diverse sample of 613 university students was surveyed to study their cyberbullying experiences in high school and college. Nineteen percent of the sample reported being a victim of cyberbullying in college and 35% of this subsample reported being cyberbullied in high school. Additional findings and practical implications are presented.